Influence of process parameters on the strength of oil palm kernel shell pellets - Lai, Zhenyue; Chua, Han; Goh, Aaron (Springer, 2013)
In this study, the influence of processing and storage parameters on the strength of oil palm kernel shell pellets was determined. The strength of the pellets increased with compaction pressure but pelletizing pressures above 188 MPa had little effect on the pellet strength. At these high pressures, the pellets achieved no or near-zero porosities, indicating that the maximum strength was achieved. The diametrical tensile strengths of the pellets were much weaker than the compressive strengths when compacted at the same compaction pressure. The pellet strengths were found to increase with longer hold times during the compaction process. This was due to a continuous decrease in porosities until near-zero porosities were achieved, when increasing the hold time no longer led to further strengthening of the pellets. The time-dependent characteristic of the pellet strength was also reflected in the reduction in strength as compaction speed was increased. The strength of the pellets decreased significantly after 1 day (24 h) of storage, with a higher decrease observed when the pellets were stored under a higher humidity condition. These changes during storage could create difficulties during handling and transportation and may affect gasification performance.